(untitled) (European Journal of Education and Psychology, 2011)
A human being conceives of him or herself as being in a constant interrelation with varied educative agents, through which diverse values and attitudes flow. The present study seeks to verify the suitability of the physical-sport leisure model to promote social values that optimize an adolescent’s ability to integrate and socialize, while considering the family unit to be the cardinal agent in this process. The scope of the analysis, therefore, explores the perceptions of young people, parents, and professors regarding the social dimensions of these values. To this end, a complementary methodology has been used that works with quantitative techniques -employing a questionnaire as an instrument of measurement- and with qualitative techniques, specifically a contextual analysis of four discussion groups. The results confirm the following: that a physical-sport leisure model is, a priori, a neutral axiological context, with the potential to encourage as many values as counter-values; that the family unit constitutes both an educative and fundamental agent that is able to engender physical-sport habits in the adolescent; and that in spite of parents defending the practice of social values, teachers and young people sometimes reproach them for not valuing it in just measures, potentially leading to the neglect of the above lifestyle.